Dance training intensity at 11–14 years is associated with femoral torsion in classical ballet dancers. Issue 4 (23rd March 2006) - Hamilton, D; Aronsen, P; Løken, J H; Berg, I M; Skotheim, R; Hopper, D; Clarke, A; Briffa, N K
Abstract : Objective: To examine in a cross sectional study the influence of femoral torsion (FT) and passive hip external rotation (PER) on turnout (TO). Starting age, years of classical ballet training, and current and past dance training intensity were assessed to determine their influence on FT, PER, and TO in pre-professional female dancers. Methods: Sixty four dancers (mean (SD) age 18.16 (1.80) years) were recruited from four different dance training programmes. They completed a dance history questionnaire. FT was measured using a clinical method. PER was measured with the subjects prone, and TO was measured with the subjects standing. Results: Mean TO was 136°, mean unilateral PER was 49.4°, and mean FT was 18.4°. A positive correlation was observed between PER combined (PERC) and TO ( r = 0.443, p<0.001). A negative association was found between FT combined (FTC) and PERC ( r = −0.402, p = 0.001). No association was found between starting age or years of classical ballet training and FTC, PERC, or TO. Dancers who trained for six hours a week or more during the 11–14 year age range had less FT than those who trained less (mean difference 6°, 95% confidence interval 1.4 to 10.3). Students currently training for longer had higher levels of TO (p<0.001) but comparable PERC and FTC. Conclusion: FT is significantly associated with PERC. Dancers who trained for six hours a week or more at 11–14 years of age had significantly less FT. FTC had a significant influence on PERC, but no influence on the execution of TO.